Incidentally discovered goblet cell carcinoid clinically presenting as acute intestinal obstruction: A case report with review of literature - Nishat Afroz; Nida Shamim; Lateef Ahmed Sofi; Syed Amjad Ali Rizvi (Wolters Kluwer Medknow Publications, 2014)
Goblet cell carcinoid (GCC) is a rare variant of carcinoid tumor that exclusively involves the appendix. It usually occurs in 5 th -6 th decade with the most common clinical presentation being acute appendicitis. The natural history of this tumor is intermediate between carcinoids and adenocarcinomas. We here report a case of GCC diagnosed incidentally in a patient presenting with acute intestinal obstruction. Ultrasonographic examination supported the clinical diagnosis of acute intestinal obstruction, following which the patient underwent laparotomy and resection of ileum along with appendix was done. On gross pathological examination, a nodular growth was present on the tip and body of appendix that was yellow in color with a semi-solid to mucoid consistency on cut section. On microscopy, lakes of mucin with few acinar structures floating in them were seen. The submucosa as well as serosa were infiltrated by clusters of goblet cells and well-formed acini, with little atypia. Glands and nests were positive for per-iodic acid Schiff and immunohistochemistry showed focal chromogranin positivity in glandular structures, thereby confirming the diagnosis of GCC. Although the prognosis of GCC is better than adenocarcinomas, it is one of the carcinoids having a poorer outcome when compared with other variants of carcinoid tumor. Therefore, it is important to rule out other differential diagnoses of goblet cell carcinoid, the most important being mucinous adenocarcinomas.